Phylogenetic relationships among Malaysian Puntius and its allies (pisces: cyprinidae) - Moghaddam, Faezeh Yazdani (2012)
The variation of criteria among authors and the discrepancies between morphological and molecular data generated a troublesome situation concerning the delimitation of the genus Puntius, which remains as yet unresolved. This is the first documentation on phylogenetic relationships among Puntius species in Malaysia integrating classical morphometrics, geometric morphometrics and molecular techniques. Morphological and phylogenetic studies were conducted on 10 Malaysian Puntius species and their allies, namely P. bulu, P. fasciatus, P. schwanenfeldii, P. binotatus, P. evereti, P. tetrazona partipentazona, P. tetrazona hexazona, P. daruphani, P. lateristeriga and P. gonionotus obtained from five locations in Peninsular Malaysia. A total of 312 samples were analysed. The quantitative data were analysed using analysis of variance (ANOVA), Principal Component Analysis (PCA) and Discrimination Function Analysis (DFA). Discriminating efficiency was highest in the truss network morphometric followed by classical morphometric and meristic techniques. In geometric morphometric Canonical Variate Analysis was performed on the total shape matrix. Results were further supported by sequencing of the cytochrome c oxidase subunit I (Cox1, 501 bp) and cytochrome b (Cytb, 857 bp) mitochondrial genes, and recombination activating gene (Rag2, 860 bp ) and beta actin (β-actin, 911) nuclear genes. A combination of mitochondrial and nuclear data for phylogenetic relationships analysis was conducted from 39 representative samples of Puntius species. The phylogeny among taxa was constructed through Neighbor joining (NJ), Maximum parsimony (MP), Maximum likelihood methods (ML) and Bayesian inference (BI). The result of genetic distances and haplotype diversities among species were high indicating a complex genus of Puntius. In an attempt to confirm the phylogenetic position of Puntius within common cyprinids in Southeast Asia, dataset of Puntius in Peninsular Malaysia was complemented by Cytb and Rag2 sequences for different species of Puntius and common cyprinids belonging to Southeast Asia in GenBank. The tree with Maximum likelihood scores was chosen as the best tree. Clades retrieved from different trees strongly supported that subfamily Cyprininae and four selected genera within Puntius complex were monophyletic group, while tribe Barbinini, Cyprinini and genus Puntius were not monophyletic. Results of the combined data set were similar with the taxonomic hierarchy based on geometrical morphometric analyses. Divergence time estimated using a combination of molecular data from multiple DNA loci and fossil evidence for Puntius among Cyprininae was about 26.85 million years ago (26.08-28.22) and supported their early Oligocene origin.